Jogging versus Weight Training Combined with Intermittent Fasting for Reducing Body Fat in Overweight Male University Students - Reshandi Nugraha; Muhammad Dzikry Abdullah Al Ghazaly; Asep Sumpena; Mohamad Nizam Nazarudin; Naufal Nur Fadhillah Karim (Journal of Sport Science and Education, 2026)
Excess body fat among overweight university students is a growing health concern associated with increased metabolic risk and reduced physical well-being. Combining exercise with intermittent fasting (IF) has emerged as a promising strategy to improve body composition. This study examined the effects of jogging with IF and weight training (WT) with IF on body fat reduction in overweight male university students. Using a quasi-experimental pretest-posttest design, 34 participants (aged 19–21 years; BMI > 27 kg/m²) were randomly assigned to jogging + IF (n = 17) or WT + IF (n = 17). Both interventions were performed for four weeks, three to four sessions weekly, during fasting hours before iftar. Body fat was assessed using the InBody test, while dietary compliance was monitored through the Red Secret app. Both groups showed significant reductions in body fat (p < 0.001). The jogging + IF group achieved a greater mean reduction (3.52 ± 0.37; 12.96%) than the WT + IF group (3.20 ± 0.23; 11.59%). However, between-group differences were not statistically significant (Welch's t = -2.039, p = 0.052), although the effect size (Cohen's d = -0.699) indicated a moderate-to-large practical difference. Both interventions effectively reduced body fat with comparable overall outcomes.